Patient-Clinic Communication App - Vlad-Andrei LĂZĂRESCU (Applied Medical Informatics)
The Patient-Clinic Communication App aims to improve communication between patients and healthcare facilities. Its primary purpose is to enable patients to manage their health easily and conveniently from anywhere. However, currently, patients are facing challenges such as long waiting times while trying to schedule an appointment, limited access to non-digital health records and difficulties in maintaining a good communication with their doctor. The app covers functionalities such as scheduling appointments and aiding in diagnosis. It allows patients to easily access their reports like receipts, scans and medical documents. Besides these, some other key features that are implemented inside the application consist of emergency report capabilities, connection with labs for medical testing, meetings and notifications. Both patients and doctors can create accounts to connect through the application, facilitating communication and access to essential features. Users can communicate through the built-in chat feature or by joining a pre-scheduled virtual appointment. In order to ensure data confidentiality, the information about the user is visible only to their contacts, while the medical files can be seen only by the user and their doctors. The application is built using React Native for the frontend, which simplifies the development of different mobile operating systems, Node.js for the backend and a FireBase database to store the data.